2018
DOI: 10.1016/j.chest.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in Asthma

Abstract: 45 46There is increasing interest in the therapeutic utility of vitamin D in asthma, supported by a 47

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 69 publications
2
54
0
4
Order By: Relevance
“…23 A recent Cochrane review of randomized clinical trials identified high-quality evidence that vitamin D supplementation reduced the risk for asthma exacerbations, although too few pediatric trials were included to permit definitive conclusions for children. 24,25 Although observational studies have consistently found significant associations between low vitamin D levels and increased susceptibility to respiratory infections, randomized clinical trials examining the effects of vitamin D supplementation on the risk for respiratory infections have had conflicting findings that are due, in part, to differences in the baseline status of the participants, the duration of the studies, and the amount and frequency of dosing. [26][27][28][29] Children with sickle cell disease are at high risk for vitamin D deficiency due to limited sun exposure, dark skin color, and poor nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…23 A recent Cochrane review of randomized clinical trials identified high-quality evidence that vitamin D supplementation reduced the risk for asthma exacerbations, although too few pediatric trials were included to permit definitive conclusions for children. 24,25 Although observational studies have consistently found significant associations between low vitamin D levels and increased susceptibility to respiratory infections, randomized clinical trials examining the effects of vitamin D supplementation on the risk for respiratory infections have had conflicting findings that are due, in part, to differences in the baseline status of the participants, the duration of the studies, and the amount and frequency of dosing. [26][27][28][29] Children with sickle cell disease are at high risk for vitamin D deficiency due to limited sun exposure, dark skin color, and poor nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple epidemiological studies have identified strong associations between vitamin D deficiency and different aspects of asthma [5]. In support of these associations being biologically important, there are now convincing findings from clinical trial meta-analyses that show vitamin D supplementation of appropriate patients significantly reduces their rate of exacerbations requiring systemic corticosteroids [3,6,7]. Not only is the effect statistically significant but also clinically significant with a recent individual patient data meta-analysis by Jolliffe and colleagues finding an adjusted incidence rate ratio of 0.74 in favor of reduced exacerbations with vitamin D supplementation versus placebo (95% confidence interval 0.56-0.97; p = 0.03) [6].…”
mentioning
confidence: 96%
“…Despite the potential for interventions targeted at 'correcting' the individual's exposome to be cost-effective and extremely safe compared to traditional pharmacotherapies, comparatively few trials have been undertaken of such interventions in asthma. Vitamin D stands out as the environmental factor most rigorously investigated in asthma and lessons learnt from these studies are important in considering other potential treatments for asthma that target the exposome [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations